Tribal worlds : critical studies in American Indian Nation building - Hosmer, Brian C., 1960-; Nesper, Larry, 1951- (Albany : State University of New York Press, 2013)
This collection explores how Indigenous nationhood has emerged and been maintained in the face of aggressive efforts to assimilate Native peoples.
Introduction / Brian Hosmer and Larry Nesper -- Definitions. Tuscarora Political Domains / Anthony F. C. Wallace ; 'To Renew Our Fire' : Political Activism, Nationalism,and Identity in Three Rotinonhsionni Communities / Gerald F. Reid ; Kinship as an Assertion of Sovereign Native Nationhood / Christina Gish Hill ; Marked by Fire : Anishinaabe Articulations of Nationhood in Treaty-Making with the United States and Canada / Heidi Kiiwetinepinesiik Stark ; Imagining Un-Imagined Communities: The Politics of Indigenous Nationalism / Sebastian F. Braun -- Manifestations. Articulating a Traditional Future: Makah Sealers and Whalers, 1880-1999 / Joshua L. Reid ; Beyond Folklore: Historical Writing and Treaty Rights Activism in the Bad River WPA / Chantal Norrgard ; Anishinaabe Gathering Rights and Market Arts : The WPA Indian Handicraft Project in Michigan / Adriana Greci Green ; We Worked and Made Beautiful Things : Kiowa Women, Material Culture, and Peoplehood, 1900-1939 / Jenny Tone-Pah-Hote.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Indians of North America -- Politics and government; Indians of North America -- Government relatins; Indians of North America -- Civil rights; Nationalism -- United States; Nation-building -- United States; Self-determination, National -- United States; United States -- Politics and government; United States -- Race relations; Nationalisme -- États-Unis.; Reconstruction d'une nation -- États-Unis.; Droit des peuples à disposer d'eux-mêmes -- États-Unis.; États-Unis -- Politique et gouvernement; États-Unis -- Relations raciales; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights; Indians of North America -- Civil rights; Indians of North America -- Politics and government; Nation-building; Nationalism; Politics and government; Race relations; Self-determination, National; United States